Autonomous Aerial Water Sampling. Issue 8 (14th May 2015) - Ore, John‐Paul; Elbaum, Sebastian; Burgin, Amy; Detweiler, Carrick
Abstract : Obtaining spatially separated, high‐frequency water samples from rivers and lakes is critical to enhance our understanding and effective management of freshwater resources. In this work, we present an aerial water sampler and assess the system through field experiments. The aerial water sampler has the potential to vastly increase the speed and range at which scientists obtain water samples while reducing cost and effort. The water sampling system includes 1) a mechanism to capture three 20 ml samples per mission, 2) sensors and algorithms for altitude approximation over water, and 3) software components that integrate and analyze sensor data, control the vehicle, drive the sampling mechanism, and manage risk. We validate the system in the lab, characterize key sensors, develop a framework for quantifying risk, and present results of outdoor experiments that characterize the performance of the system under windy conditions. In addition, we compare water samples from local lakes obtained by our system to samples obtained by traditional sampling techniques. We find that even winds of 5.8 m/s have little impact on the water sampling system and that the samples collected are consistent with traditional techniques for most properties. These experiments show that despite the challenges associated with flying precisely over water, it is possible to quickly obtain scientifically useful water samples with an unmanned aerial vehicle.